Economic decision-making in morning/evening-type people as a function of time of day. (7th February 2017) - Correa, Angel; Ruiz-Herrera, Noelia; Ruz, Maria; Tonetti, Lorenzo; Martoni, Monica; Fabbri, Marco; Natale, Vincenzo
ABSTRACT: Decision-making is affected by psychological factors like emotional state or cognitive control, which may also vary with circadian rhythmicity. Here, we tested the influence of chronotype (32 morning-type versus 32 evening-type) and time of day (9 a.m. versus 5 p.m.) on interpersonal decision-making as measured by the Ultimatum Game. Participants had to accept or reject different economic offers proposed by a virtual participant. Acceptance involved distribution of gains as proposed, whereas rejection resulted in no gain for either player. The results of the game showed a deviation from rational performance, as participants usually rejected the unfair offers. This behaviour was similar for both chronotype groups, and in both times of day. This result may reflect the robustness of decision-making strategies across standard circadian phases under ecological conditions. Furthermore, morning-types invested more time than evening-types to respond to high-uncertainty offers. This more cautious decision-making style of morning-types fits with our finding of higher proactive control as compared to evening-types when performing the AX-Continuous Performance Task. In line with the literature on personality traits, our results suggest that morning-types behave with more conscientiousness and less risk-taking than evening-type individuals.